Evaluation of resident biocontrol agents as seed treatments against ginger rhizome rot - B.C. LODHA; J. WEBSTER2, D. RAM1, KUSUM MATHUR1 (Indian Phytopathology, 2002)
Resident isolates of biocontrol agents (BCAs) Trichoderma harzianum, T. aureoviride and Gliocladium virens and a non-resident isolate of T. viride were evaluated for suppression of ginger rhizome rot, a rhizome and seedborne disease caused by Fusarium solani or Pythium myriotylum or both. Rhizomes pelletted with BCA (2.7-3.1 x 104 c.f u./g formulation) were planted in two sets of pots, one with sterilized but pathogen infested soil, and another with unsterilized, rhizome rot infected field soil. All the four BCAs could establish in ginger rhizosphere and rhizomeplane, and significantly increased in population density (0.82-3.67 x 105 c.f.u./g soil) (of T. harzianum, maximum) and reduced that of Fusarium spp., correlated well with reduction of thedisease and significant increase in the yield. The trend of efficacy of each BCA observed in the unsterilized rhizome rot infested field soil was confirmed in sterilized, pathogen-infested soil.